2022
DOI: 10.1155/2022/6957580
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy Investigation of TACE Combined with Lenvatinib and Sintilimab in Intermediate-Stage Hepatocellular Carcinoma

Abstract: Objective. To evaluate the effectiveness of transarterial chemoembolization (TACE) combined with lenvatinib and sintilimab in treating patients with midstage hepatocellular carcinoma (HCC). Methods. Sixty-two patients with midstage HCC were enrolled in this study. All of them were firstly treated in our hospital between September 1, 2019, and March 1, 2020. According to different treatment regimens, they were divided into the control group (31 cases, TACE group) and the observation group (31 cases, TACE combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The titles and abstracts of the remaining articles were carefully read and 11 studies were included. The text of these 11 studies were read in detail and 7 studies were finally included in the meta-analysis (25,26,(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…The titles and abstracts of the remaining articles were carefully read and 11 studies were included. The text of these 11 studies were read in detail and 7 studies were finally included in the meta-analysis (25,26,(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%